PROSES REKRUTMEN DAN SELEKSI PERUSAHAAN KELUARGA (STUDI KASUS SEKTOR USAHA KECIL DAN MENENGAH DI KOTA PALEMBANG) - Dedi Rianto Rahadi; Filda Rahmiati (FIRM Journal of Management Studies, 2017)
Recruitment and selection is one of the planning process within a company. The family company is no exception to prepare recruitment and selection to obtain the appropriate employee with the needs by promoting competence and professionalism. The purpose of research to find out how the process of recruitment and selection of family companies, especially small and medium enterprises (SMEs) in the city of Palembang. Research methodology used with qualitative approach, where the research process is done based on the understanding of the methodology that investigate a social phenomenon and human problems. The results showed that the recruitment and selection process still uses the centralization technique, where the family still plays an important role in determining the employees. Employee selection is only short-lived and employee status more work as part-time employee. Suggested suggestions, family companies should keep professionalism and competence priority by providing an open space for everyone in the recruitment and selection process.